Carbon and nitrogen footprint optimization of ammonia as an automotive fuel - Angeles, Donna A. (Animo Repository, 2017)
The transportation sector is one of the top contributors to global CO2 emissions, which is why focus is given to feasible alternatives to conventional automotive fuels. Recent research suggests that ammonia is a potential alternative automotive fuel due to its favorable physical and chemical properties and the mature infrastructure for its production and handling. However, there remains the question of whether ammonia can be a sustainable alternative automotive fuel. The energy-intensive production process, the need to be coupled with a secondary fuel, and the release of reactive nitrogen emissions are two major issues with the use of ammonia. To rigorously assess its potential, a comparative well-to-wheel life cycle assessment (LCA) of selected ammonia-based fuel cycles was done using carbon and nitrogen footprint as environmental indicators. Two conventional fossil fuel-based ammonia production processes and two proposed biomass-based processes were considered, namely: steam reforming, partial oxidation, a cyanobacterial process (Anabaena process), and a woodbased process (Salix process). For vehicles powered by internal combustion engines (ICEV) three types of secondary fuels were considered: gasoline, diesel, and dimethyl ether (DME). The. For comparison purposes, a theoretical scenario is also assumed wherein a generator set powered by ammonia-diesel mixture is used to produce electricity for electrical vehicles (EVs). The LCA was coupled with fuzzy life cycle optimization (LCO) and global sensitivity analysis via design of experiments (GSA/DOE) to identify the optimal system configuration and to determine the factors with most significant influence to the optimal solution. This study determined an optimal solution that uses ICEV in the vehicle operation phase and another optimal solution that uses fuel cell vehicle (FCV). Results show that ammonia produced from the Salix process with DME as the secondary fuel is the best option for ICEV, while ammonia from the Anabaena process is the best choice for FCV, which implies that proposed biomass-based processes may provide an advantage in vehicles in terms of carbon and nitrogen footprint production. GSA/DOE results show that the end-user vehicle fuel economy has the most significant influence on the optimal solution for both ICEV and FCV, which means that efforts to improve ammonia-based fuel cycles must concentrate the most on improving the fuel economy of ICEVs and FCVs.